2004
DOI: 10.1189/jlb.0803391
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophil degranulation in the allergic lung of mice primarily occurs in the airway lumen

Abstract: Eosinophil degranulation is thought to play a pivotal role in the pathogenesis of allergic disorders. Although mouse models of allergic disorders have been used extensively to identify the contribution of eosinophils to disease, ultrastructural evidence of active granule disassembly has not been reported. In this investigation, we characterized the degree of eosinophil activation in the bone marrow, blood, lung tissue, and airways lumen [bronchoalveolar lavage fluid (BALF)] of ovalbumin-sensitized and aero-cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
48
1
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 44 publications
(93 reference statements)
3
48
1
1
Order By: Relevance
“…In contrast, most reports suggest that mouse eosinophils display little to no degranulation (see for example, Refs. 5 and 40) and in the few studies describing this phenomenon, eosinophil degranulation was limited to cells in the airway lumen and to piecemeal release (36,41). Nonetheless, the apparent lack of extensive degranulation of mouse eosinophils may also, in part, reflect inadequacies of existing models for such studies.…”
Section: Discussionmentioning
confidence: 97%
“…In contrast, most reports suggest that mouse eosinophils display little to no degranulation (see for example, Refs. 5 and 40) and in the few studies describing this phenomenon, eosinophil degranulation was limited to cells in the airway lumen and to piecemeal release (36,41). Nonetheless, the apparent lack of extensive degranulation of mouse eosinophils may also, in part, reflect inadequacies of existing models for such studies.…”
Section: Discussionmentioning
confidence: 97%
“…In spite of the commonly held perspective proposing that eosinophil secondary granule proteins are significant contributors to histopathologies and lung dysfunction, the definition of the cellular and molecular events surrounding degranulation has been severely limited by the inability of established mouse models of aeroallergen challenge to display the extensive eosinophil degranulation found in human subjects with asthma (38,40,53). This lack of concordance has typically been explained as either a limitation of mouse models (reviewed in Reference 54), shortcomings linked with available allergens administered to mice (55), and/or the allergen challenge protocols themselves (56,57).…”
Section: Discussionmentioning
confidence: 99%
“…Also, MBP has been found on damaged epithelial surfaces and in mucus plugs in patients who died from status asthmaticus (16), showing that severe asthma is associated with a substantial presence of eosinophils and MPB within the airway lumen. Indeed, Clark et al (4) recently showed that the majority of eosinophil degranulation predominately occurs in the lumen of the airways. Furthermore, we have previously shown in an airway tube system that cationic proteins also disrupt epithelial function when present to the basolateral aspect of the tissue but do not affect airway responsiveness when presented to the outside of the airway (7).…”
Section: Discussionmentioning
confidence: 99%